-2-2(x-3)+4x=-(-x+1)

Simple and best practice solution for -2-2(x-3)+4x=-(-x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2-2(x-3)+4x=-(-x+1) equation:


Simplifying
-2 + -2(x + -3) + 4x = -1(-1x + 1)

Reorder the terms:
-2 + -2(-3 + x) + 4x = -1(-1x + 1)
-2 + (-3 * -2 + x * -2) + 4x = -1(-1x + 1)
-2 + (6 + -2x) + 4x = -1(-1x + 1)

Combine like terms: -2 + 6 = 4
4 + -2x + 4x = -1(-1x + 1)

Combine like terms: -2x + 4x = 2x
4 + 2x = -1(-1x + 1)

Reorder the terms:
4 + 2x = -1(1 + -1x)
4 + 2x = (1 * -1 + -1x * -1)
4 + 2x = (-1 + 1x)

Solving
4 + 2x = -1 + 1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
4 + 2x + -1x = -1 + 1x + -1x

Combine like terms: 2x + -1x = 1x
4 + 1x = -1 + 1x + -1x

Combine like terms: 1x + -1x = 0
4 + 1x = -1 + 0
4 + 1x = -1

Add '-4' to each side of the equation.
4 + -4 + 1x = -1 + -4

Combine like terms: 4 + -4 = 0
0 + 1x = -1 + -4
1x = -1 + -4

Combine like terms: -1 + -4 = -5
1x = -5

Divide each side by '1'.
x = -5

Simplifying
x = -5

See similar equations:

| 4x+6+x-9=32 | | 12+2r=76 | | 24x^2-73x=-1 | | 10x+60=360 | | -8xy+2=8d | | 3x+2.4=7.6 | | -5=1/2n | | 12a+5b=52 | | 9ab-6c=4d | | 9x-4(2-x)=7x+16 | | 11s+7t=97 | | 12a+5b=526 | | x^2+2x=108 | | x^2+11x=13 | | (100*x)*0.1=100 | | F(3a)=2x^2-3x+1 | | 35=7(3x-1) | | 5x+2-3x=5+2x-3 | | -xy-42=7w | | 2x+y-3z=7 | | 5(e+7)=11 | | 2(z-4)=0.5(3z-1) | | 8y+8x=-4 | | 38=-6v-7v-27 | | 8. 4(y+3)=24 | | 7p+8q= | | 9n^4-30n^2+25=0 | | 23-3x=16+4x | | 10n^2+41n-18=0 | | 10-3y=x | | 5(X+3)=6x-8 | | fx=x^4-4x^2+15 |

Equations solver categories